Sovereigns and Financial Intermediaries Spillovers - Tabarraei, Hamid; Pierrard, Olivier; Rouabah, Abdelaziz (Washington, D.C. : International Monetary Fund, 2019)
We examine the spillover effects between sovereigns and banks in a model with a heterogeneous banking system. An increase in sovereign's default risk affects financial intermediaries through two channels in this model. First, banks' funding costs might increase, inducing higher interest rates on loans and bonds and a cut back in these assets. Second, financial regulator's risk-weighted asset framework would assign higher weights to lower quality assets, implying a portfolio rebalancing and more deleveraging. While capital adequacy requirements weaken the impact of shocks emerging from the real economy, they amplify the effect of shocks on banks' balance sheets.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet